Surgery and the relative index in elliptic theory - V. E. Nazaikinskii; B. Yu. Sternin (Abstract and Applied Analysis)
This is a survey article featuring the general index locality principle introduced by the authors, which can be used to obtain index formulas for elliptic operators and Fourier integral operators in various situations, including operators on stratified manifolds and manifolds with singularities.